The first steps of industrial hygiene and occupational toxicology at the Clinica del Lavoro di Milano under the guidance of Luigi Devoto - Fustinoni, Silvia; Riva, Michele Augusto (La Medicina del Lavoro, 2019)
Introduction: The Clinica del Lavoro, the first clinic for occupational diseases of the world, was inaugurated in Milan on 20 March 1910; its first director was Luigi Devoto, who was in charge until 1935. The purpose of this work is to review the activities of industrial hygiene and toxicology carried out at the Clinica del Lavoro under the guidance of Devoto. Methods: Documents published by the Istituti Clinici di Perfezionamento, a group of clinics of which the Clinica del Lavoro was part, record the birth and organization of this structure and the presence of a laboratory of chemistry; documents by Devoto and other authors were also retrieved to extrapolate specific information on activities of industrial hygiene and toxicology. Results: The Clinica del Lavoro, at the time of its inauguration, included four laboratories: of chemistry, clinical physics, histopathology and bacteriology. The chemistry lab was located on the first floor and was composed of 6 well-lit rooms, modernly equipped with work benches that could accommodate 12 people. In Devoto’s view, the chemistry laboratory, supported by that of clinical physics, had to assess the toxicological properties of chemicals commonly found in the workplace and to reveal the mechanisms of induction of damage to humans. In the first 30 years of activity, the Clinica del Lavoro investigated various diseases deriving from exposure to chemical agents, including saturnism, or lead intoxication, mercurialism, phosphorism, benzolism, sulfocarbonism, dust diseases. Several assays were developed and applied to measure toxicants in different biological and environmental mean as evidenced by scientific publications starting from 1920. Conclusion: In Devoto’s view, industrial hygiene and toxicology were essential tools for the research and prevention of occupational diseases since the first years of activity of the Clinica del Lavoro.